Mechanical stress and ATP synthesis are coupled by mitochondrial oxidants in articular cartilage. Issue 2 (28th August 2012) - Wolff, Katherine J.; Ramakrishnan, Prem S.; Brouillette, Marc J.; Journot, Brice J.; Mckinley, Todd O.; Buckwalter, Joseph A.; Martin, James A.
Abstract Metabolic adaptation of articular cartilage under joint loading is evident and matrix synthesis seems to be critically tied to ATP. Chondrocytes utilize the glycolytic pathway for energy requirements but seem to require mitochondrial reactive oxygen species (ROS) to sustain ATP synthesis. The role of ROS in regulating ATP reserves under a mechanically active environment is not clear. It is believed that physiological strains cause deformation of the mitochondria, potentially releasing ROS for energy production. We hypothesized that mechanical loading stimulates ATP synthesis via mitochondrial release of ROS. Bovine osteochondral explants were dynamically loaded at 0.5 Hz with amplitude of 0.25 MPa for 1 h. Cartilage response to mechanical loading was assessed by imaging with dihydroethidium (ROS indicator) and a Luciferase‐based ATP assay. Electron transport inhibitor rotenone and mitochondrial ROS scavenger MitoQ significantly suppressed mechanically induced ROS production and ATP synthesis. Our findings indicate that mitochondrial ROS are produced as a result of physiological mechanical strains. Taken together with our previous findings of ROS involvement in blunt impact injuries, mitochondrial ROS are important contributors to cartilage metabolic adaptation and their precise role in the pathogenesis of osteoarthritis warrants further investigation. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 191–196, 2013